PENGARUH KEBISINGAN DENGAN GANGGUAN PENDENGARAN DI DUSUN JAGALAN TEGALTIRTO BERBAH SLEMAN - Putri Sayidah; Novita Sekarwati; Dewi Wahyu Indriyani (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2016)
ABSTRACTHearing disorders caused by noise (noise induced hearing loss or NIHL) is a deaf which is caused by exposure of loud noise in a considerable period of time and usually it is caused by environmental  noise. There are many factors making people deaf easily such as intensity, high noise frequency,  the period of exposure by noise, individual sensitivity, and many more. According to the preliminary research, the noise intensity measuring in Dusun Jagalan, Tegaltirto, Berbah, Sleman produces average results that is 63,61 dB that means it exceeds of threshold number. The general objective in this research is to ﬁ nd out the effect of noise to hearing disorders in dusun jagalan, Tegalrejo, Berbah, Sleman. The speciﬁ c objective is to ﬁ nd out the noise and noise disorders in society living in RT 5 Dusun Jagalan, Tegaltirto, Berbah, Sleman.This research uses cross sectional approach method and this non-experimental research correlation quantitative research design. This research uses total sampling technique. Sample in this research is 8 points of noise intensity measuring and people with hearing disorders are 30. The result of noise intensity measuring shows the average of 62,04dB (A) and hearing disorders measuring shows the result that 14 people have deaf criteria hearing level of 1.It can be concluded that correlation test using product moment it is known sig (2-tailed)=0,122>0,05 it means that there is no effect between noise and hearing disorders of people living in RT 5 Dusun Jagalan, Tegaltirto, Berbah, Sleman. 14 people have hearing disorders with 1 deaf criteria and noise intensity 62,04 dB that it exceeds of the threshold number.